Importance of Blood Glucose Monitoring in Pregnant Females - Maria Ghafoor, Aisha Qayyum, Asifa Ghazi, Summaiya Khalid, Misbah Aftab, Afshan Shahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of gestational diabetes mellitus (GDM) among pregnant females. Study Design: Cross-sectional study. Place and Duration: Department of Gynecology and Obstetrics, and department of Pathology, Dow University of health sciences, From February 2021 to January 2022. Methodology: Five hundred pregnant ladies with gestational age between 24-28 weeks with any parity were included. These women were challenged with 75 grams of oral glucose solution and blood glucose levels were estimated at one-hour post-prandial. The cut-off limit was set to 140 mg/dl and women with more than this value were subjected to a 2 hr 75 grams oral glucose tolerance test to confirm the diagnosis of GDM. Results: Out of a total of 500 pregnant women, the mean age, gestational age and BMI were 26.4±4.3 years, 27.0±10.2 weeks and 27.6±4.3 kg/m2. There were 59 (11.8%) women who were found to have a positive glucose challenge test (GCT) while the remaining 441 (88.2%) had plasma glucose below 140 mg/dl. Furthermore, 59 OGTT results showed that 43 (8.6%) women had GDM. Women with GDM had significantly higher age (p<0.0001), higher BMI (p=0.0064) and multigravidity (0.0191) Practical Implications: Oral glucose challenge test can be administered in all pregnant women particularly in high risk individuals. Conclusion: The frequency of GDM was high. Pregnant ladies should be screened for GDM in time to prevent further complications during and after pregnancy. Keywords: Blood glucose, gestational diabetes mellitus, post-prandial.